Investigating The Effects of Self-Directed Dialogue on Freshman English Learners Speaking Power in Expressing Opinions - Masita; Sitti Maryam Hamid; Junaid (English Language Teaching Methodology, 2026)
Speaking proficiency is a crucial productive competence for students of English Language Education; however, first-year learners often experience difficulties in articulating opinions orally due to limited opportunities for autonomous practice and high levels of speaking anxiety. Although previous studies have demonstrated the effectiveness of self-directed dialogue in enhancing speaking skills, research specifically addressing freshman learners during their critical transition period remains limited, particularly in EFL contexts with minimal out-of-class English exposure. This study aims to investigate whether and how the use of self-directed dialogue influences freshman English learners’ speaking performance in terms of fluency and accuracy. Adopting a qualitative case study design, this research involved fifteen first-semester students enrolled in the English Education Program at Universitas Muhammadiyah Makassar in the 2025/2026 academic year. Data were collected through participatory observation and semi-structured interviews and analyzed using Miles and Huberman’s interactive framework. The findings indicate that self-directed dialogue contributes to improvements in speaking fluency, as reflected in reduced pauses, increased spontaneity, and clearer sentence structuring, as well as in speaking accuracy, including improved vocabulary use, sentence formation, and pronunciation. In addition, the practice fosters learner autonomy and self-confidence, supporting students’ adjustment during the transition to higher education. These findings highlight the role of self-directed dialogue as a pedagogical bridge that integrates linguistic development and learner adjustment, offering a contextually relevant contribution to EFL pedagogy. In conclusion, self-directed dialogue serves as an effective complementary strategy to support freshman learners’ speaking development, particularly in facilitating their transition toward more autonomous learning.